2011
DOI: 10.1103/physrevb.84.180401
|View full text |Cite
|
Sign up to set email alerts
|

Ground state and intrinsic susceptibility of the kagome antiferromagnet vesignieite as seen by51V NMR

Abstract: The intrinsic magnetic susceptibility and local magnetization of the near-kagome quantum magnet vesignieite, Cu3BaV2O8(OH)2, are presented as measured using 51 V NMR. The NMR line shift gives an accurate measurement of the intrinsic susceptibility of the kagome sites which closely resembles that of the quantum spin liquid herbertsmithite [A. Olariu et al. Phys. Rev. Lett. 100, 087202 (2008)]. It is therefore surprising that, at TC ≃ 9 K, a transition to a heterogeneous ground state is observed. A gradual wipe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 33 publications
5
78
1
Order By: Relevance
“…The tendency to magnetic order in paratacamites may be induced by interplane couplings through Cu defect spins at the Zn site between the kagomé layers, as well as the likely presence of a sizable Dzyaloshinsky-Moriya term. On the other hand, the nearly undistorted kagomé compound vesignieite, BaCu 3 V 2 O 8 (OH) 2 , has recently been reported to show a peculiar transition at 9 K to a partly frozen state with persisting spin dynamics 6,7 , despite no order being found in previous studies 5 . It is suggested that this order occurs owing to a large Dzyaloshinsky-Moriya interaction within the kagomé plane 6,7 .…”
Section: Discussionmentioning
confidence: 96%
“…The tendency to magnetic order in paratacamites may be induced by interplane couplings through Cu defect spins at the Zn site between the kagomé layers, as well as the likely presence of a sizable Dzyaloshinsky-Moriya term. On the other hand, the nearly undistorted kagomé compound vesignieite, BaCu 3 V 2 O 8 (OH) 2 , has recently been reported to show a peculiar transition at 9 K to a partly frozen state with persisting spin dynamics 6,7 , despite no order being found in previous studies 5 . It is suggested that this order occurs owing to a large Dzyaloshinsky-Moriya interaction within the kagomé plane 6,7 .…”
Section: Discussionmentioning
confidence: 96%
“…In the case of BaCu 3 V 2 O 8 (OH) 2 , an inhomogeneous magnetic order has been detected through NMR measurements around 9 K, below which the unwanted Curie tail grows rapidly. 15,16 We have discovered the absense of magnetic long range order in a hexagonal lattice of Ru 5+ dimers in Ba 3 ZnRu 2 O 9 down to 37 mK, where neither Curie tail nor glassy behavior is detected. The magnetic specific heat shows no anomaly below 80 K, and is found to be linear in temperature below around 5 K. These thermodynamic measurements suggest a spin-liquid like ground state in this oxide.…”
mentioning
confidence: 99%
“…This certainly affects the Ir 4+ environments and leads to a distribution of magnetic interactions on the hyperkagome lattice, especially if interactions are dominantly due to direct exchange as argued in many papers [39]. Deviations to equilateral interaction triangles have always led to transitions at T J such as observed in Volborthite [40] and Vesignieite [41,42] kagome-based compounds. Digging out why a distribution of interactions could lead to such a weak or no signature in χ and C/T respectively should be addressed theoretically which may help discriminate between models proposed for this iridate.…”
mentioning
confidence: 99%